Peculiarities of crusted scabies in immunocompromised patients - Reznichenko, N.; Резніченко, Наталія Юріївна; Kothapalli, M. K. (Запорізький державний медичний університет, 2019)
Introduction. Patients with severe immunodeficiency have conditions for the occurrence of many infectious diseases. The most unfavorable prognosis in skin diseases is crusted/Norwegian scabies which is rare and characterized by widespread crusts, hyperkeratotic lesions teeming with innumerable mites. Aim: to identify the characteristics of the course of the crusted scabies in the immunocompromised patients with steroid therapy. Materials and Method. 10 cases of crusted scabies were treated in Community Institution “Zaporizhia Regional Dermatovenereology Clinical Hospital” of Zaporizhia Regional Council during 2018 -2019 years. Standard methods of microscopic laboratory analysis and treatment were used in all patients according to National Regime.
Keywords: тези доповідей